Role of Constructed Environment for Tourism Development: A Global Trend Analysis base on Triangulated Review - Zimik, A S Sochipem; Barman, Arup (PT. Riset Press International, 2024)
The study employs a pragmatic approach to comprehend the constructed environment as a means for propelling tourism industries. Various relevant works of literature are taken into account in analyzing the impact of the constructed environment and its significance to tourism. The objectives of the study are twofold. First, it reviews the constructed environment in detail considering it in three sub-sets. These are the frame; sustenance; and nature. Second, it analyzes the global status of the constructed environment concerning tourism development. The study highlights the research lacuna to draw convincing conclusions about why the constructed environment signifies the growth of the sector. The key takeaway point from the study is the earnest need for a developed constructed environment for development of the industries. The study concludes with suggestive notes to various stakeholders to be conscious enough in understanding tourist psychology, policymaking, and resource management; which will result in economic vitality.